2020
DOI: 10.31083/j.rcm.2020.03.131
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency in association with endothelial dysfunction: Implications for patients with COVID-19

Abstract: There is emerging evidence to suggest that vitamin D deficiency is associated with adverse outcomes in COVID-19 patients. Conversely, vitamin D supplementation protects against an initial alveolar diffuse damage of COVID-19 becoming progressively worse. The mechanisms by which vitamin D deficiency exacerbates COVID-19 pneumonia remain poorly understood. In this review we describe the rationale of the putative role of endothelial dysfunction in this event. Herein, we will briefly review (1) anti-inflammatory an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 41 publications
0
38
0
Order By: Relevance
“…160 The damaged respiratory endothelium during the entrance of SARS-CoV-2 through ACE2 receptors leads to endothelial dysfunction that in turn interferes with the binding of inadequately present vitamin D to its receptor (VDR), resulting in further progression of the inflammatory process and increased risk of severity in COVID-19. 162 Lately, several researchers have confirmed the positive effects of GSH, that acts as a potent antioxidant, along with its precursor, L-cysteine, on vitamin D metabolism. 41 Thus individuals with depleted GSH become less able to overcome the oxidative stress that develops during infections.…”
Section: Consequences In Patients With Vitamin D Deficiency and Concurrent Risk Factors During Sars-cov-2 Infectionmentioning
confidence: 99%
“…160 The damaged respiratory endothelium during the entrance of SARS-CoV-2 through ACE2 receptors leads to endothelial dysfunction that in turn interferes with the binding of inadequately present vitamin D to its receptor (VDR), resulting in further progression of the inflammatory process and increased risk of severity in COVID-19. 162 Lately, several researchers have confirmed the positive effects of GSH, that acts as a potent antioxidant, along with its precursor, L-cysteine, on vitamin D metabolism. 41 Thus individuals with depleted GSH become less able to overcome the oxidative stress that develops during infections.…”
Section: Consequences In Patients With Vitamin D Deficiency and Concurrent Risk Factors During Sars-cov-2 Infectionmentioning
confidence: 99%
“…Conversely, EC dysfunction resulting from angiotensin-converting enzyme 2 (ACE2) and vitamin D receptors contributes to coronavirus disease 2019 (COVID-19)-associated vascular inflammation and coagulopathy. 1,2 Studying severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in a primate model, Koo et al showed that the development of COVID-19 caused acute interstitial pneumonia with endotheliitis in the lungs. 3 These findings strengthen the implications of EC dysfunction in COVID-19.…”
mentioning
confidence: 99%
“…Furthermore, several authors underline the association between low levels of vitamin D and pulmonary pathologies 26 , chronic pathologies associated with metabolic syndrome 4 , vascular damage 27 , thrombotic episodes 28 confirming that this deficiency associated with these conditions involves a serious risk for the development of SARS infection. Cov-2 29 .…”
Section: Resultsmentioning
confidence: 96%